Os problemas aritméticos e os métodos pedagógicos: pontos para um diálogo sobre a história da educação matemática no ensino primário alagoano (1924 - 1952) - Fernandes, Elisabete Pereira (2017)
This research had the aim to investigate which pedagogical method, synthetic or analytical, was indicated for arithmetic problems in the oficial documents and in the Teaching Magazine of Alagoas, having the studies of Costa (1931), Stanic and Kilpatrick (1989), Chervel (1990), Polya (1995), Mortatti (2009), Verçosa (2001), De Certeau (2014), Wagner Valente (2015), among others, as theoretical and methodological references. This is a historiographical research based on the principles of the cultural history. In this study were analyzed sources that bring us closer to the school culture of Alagoas of 1924 – 1952, which are: Teaching Programs (1924, 1930, 1937 and 1952) and articles of the Teaching Magazines (1927, 1929, 1930 e 1952). The analyzes indicate that, despite the initiatives of the intuitive pedagogy, the synthetic method headed the approach of the math in the Primary education of Alagoas until the decade of 1952. From that period a different pedagogical movement began to appear in official documents and pedagogical magazines, with a greater appreciation of the problems and indications of Alagoas experiences, based on the analytical method.